Evaluating the impact of an oral nutrition supplement on biochemical profile, growth, and body composition in Indian children: an in-silico study - Sringari, Sahana; Vijaykumar, Surabhi; Sherkane, Manali; Venkatesh, Megha; Gupta, Suranjana; Lomore, Karan; Venkatesh, K. V. (Frontiers in Nutrition, 2025)
BackgroundIn-silico modeling provides a valuable approach for predicting the effects of nutritional interventions on child growth, particularly in settings where large-scale human trials are challenging. Validated, population-level predictive platforms optimize dosing and intervention strategies, facilitating the development of targeted nutritional approaches that enhance growth outcomes in children.ObjectiveThis study aims to assess the impact of an oral nutrition supplement (ONS) intervention on biochemical and growth parameters of Indian children using an in-silico intervention approach.MethodsAn energetics-based modeling framework was developed to simulate the growth trajectories of children aged 6–16 years, integrating national datasets for Indian children. The model, validated with published literature, was designed to predict the effects of nutritional interventions. This study evaluated the impact of two Horlicks Oral Nutrition Supplement (ONS) formulations with varying micronutrient dosages on key growth outcomes. Various intervention scenarios were simulated, including comparisons of ONS with water vs. milk, and interventions with different nutrient compositions, such as macronutrients alone or a combination of macro- and micronutrients. The primary outcomes of the study focused on both biochemical and physical growth changes. Key serum nutrient levels were analyzed, alongside anthropometric measures such as height, weight, and body composition indicators, including fat-free mass, fat mass, and bone mineral content, over simulated periods of 4, 8, and 12 months.ResultsThe in-silico analysis predicted that two servings of Horlicks with milk significantly improved anthropometric and body composition parameters compared to both milk alone and other experimental groups. Biochemically, the Horlicks intervention led to notable increases in serum nutrient levels, which correlated with higher growth velocities and enhanced body composition relative to plain milk. The model underscored the critical role of combined macro- and micronutrient supplementation, with two servings yielding more pronounced effects than one.ConclusionThis study provides important insights into the potential benefits of Horlicks interventions for enhancing child growth outcomes. It underscores the effectiveness of computational models in the preliminary assessment of nutrition interventions, providing foundation for targeted clinical studies to improve child health and development. However, it is important to note that the model benchmarking was conducted using data from the Indian population, and the findings may not be directly applicable to other ethnicities without further validation.